Analisis Kesalahan Pengunaan Bahasa Berupa Komentar pada Postingan @Folkative, "Jepang Respon & Siap Menyambut yang Sedang Ramai, #Kabur Aja Dulu" - Tiffany, Rehilia; Muhammad Sholeh Sihombing; Renta Giofani Hutapea; Sesjya D Hutapea (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to examine language errors in comments on social media, especially on the Instagram account @folkative with the hashtag #kaburajadulu.  Errors in the use of standardized words, mixed language, slang, and punctuation are the subject of the study.  This research was conducted through a qualitative approach, which involved descriptive analysis of the collected comment data.  The results showed that the comments were dominated by informal language variations. This phenomenon includes the use of nonstandard words (“gada” for “none”), foreign language absorption (“guys”, “subtitle), and sentence structures that do not conform to standard grammar.  In addition, it has been found that pragmatics influences the way messages are conveyed by using slang to give the impression of being more relaxed and familiar.  This study emphasizes how important it is to understand Indonesian language norms in the context of social media while considering aspects of language flexibility and creativity. In conclusion, although language variations on social media reflect the dynamics of modern communication, efforts are still needed to raise awareness of the use of good and correct Indonesian.